Kajian Perubahan Ragam Genetik Tanaman Jagung (Zea mays L.) akibat Seleksi - I Wayan Sudika; I Wayan Sutresna; Dwi Ratna Anugrahwati (LPPM Universitas Mataram, 2019)
This study aimed to determine the change in total genetic diversity after eight cycles of mass selection using a technique of selection index for yield, fresh dry matter, and weight of dry harvested cob, and to find out the average of these three characters compared to the initial population. This experiment was carried out at Pringgabaya District, East Lombok Regency using Randomized Block Design (RBD) with 11 treatments, namely eight selected populations, initial populations and two hybrid varieties. Each treatment was replicated 3 times, resulted in 33 experimental units. Data obtained were analyzed using analysis of variance at 0.05 levels. Variance of phenotype is obtained from the variety of samples; while the environmental variance is defined as the average variance of the two hybrid phenotypes. Genetic diversity is obtained from the variety of phenotypes of each population minus the environmental diversity. F-test of 0.05 was performed to find out whether the genetic diversity of the eighth cycle population is the same or different to that of the genetic diversity of the initial population. The average between the initial population and the eighth cycle population was tested using the HSD-test at 0.05 levels. The results showed that the total genetic variation in the population from the eighth cycle selection for yield, harvested dry weight of cobs, and fresh dry matter of maize were smaller than the genetic diversity of the initial population. The average yield, harvested dry cob weight and fresh dry matter weight of population of the eighth cycle selection are higher than the initial population